Pendidikan Dakwah Muhammad Quthb - Yakin, Ainul (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
The purpose of this study is to find out Muhammad Quthb's thoughts on da'wah education. This research uses the Library Research method, the source of the data is taken from Muhammad Qutb's books relating to education and da'wah. After the data is collected, it is carried out by critical and systematical analysis in the investigated problem. This research uses a descriptive analysis method, which describes or explain all of datas, then analyze them systematically. This research concludes that preaching education according to Muhammad Quthb is completed human education, it is not separated by other aspect of human nature.